Identify the role of school administration in achieving institutional excellence for workers in light of the Corona pandemic in the schools of Zarqa Governorate - Odeh, Murad Hamdallah Muhammad (Journal of Educational and Psychological Sciences, 2022)
This study aimed to identify the role of school administration in achieving institutional excellence for workers in light of the Corona pandemic In the schools of Zarqa Governorate. The study followed the descriptive approach; Where a questionnaire was used to measure the role of school administration in institutional excellence among workers in light of the Corona pandemic, and it was distributed to a sample of (100) principals of public education schools in the Kingdom of Jordan in Zarqa Governorate, and the study reached several results, most notably that the role of school administration in Achieving institutional excellence among workers in light of the Corona pandemic came to a high degree, and the study also showed that there are no statistically significant differences for the variables: (gender, educational qualification, years of experience), and the study made several recommendations; The most important of which was increasing the skill of school principals in exercising the role of school administration through training courses, increasing the powers entrusted to them, and providing schools with an advanced electronic network.
Keywords: school administration; administrative excellence; school administrations; Corona pandemic